REFLEKSI DAURAH TADRIBIYAH DI UNIVERSITAS UMM AL QURA MEKKAH SAUDI ARABIA - Permana, Farid (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
Almost of all universities in Saudi Arabia have Arabic learning program for non Arab student, one of them is Arabic language institute for non Arabic speakers at Umm Alqura university in Mecca. As a holders responsibility for developing and expanding the Arabic language, this Institute in collaboration with the kingdom of Saudi Arabia has implemented a training program to strengthen Arabic learning for Islamic boarding school teachers, teachers and Arabic lecturers from Indonesia and Senegal.on 13 Shawwal - 20 Dzulqaidah 1439 coincides with June 28 - August 4, 2018. The various learning activities in this program include Arabic language, Islam and cultural insights that designed professionally. Based on the author's observations during became a participant in this program 2018. It’s can be a very good reflection for developing Arabic learning programs in Indonesia, especially from attitude aspects, and teaching management. The author also recommends Arabic educators in Indonesia to take part in the Daurah to enrich Arabic learning techniques.